PENERAPAN PEMBELAJARAN KONSEPTUAL INTERAKTIF BERBANTUAN CMAPTOOLS UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA - muliani, desy eka (Jurnal Pelangi : Research of Education and Development, 2018)
This study is aimed to comparative analysis of concept understanding, and quantity of misconception, then student’s attitude scale after applying conceptual interactive learning with cmaptools media. This research used quasy experiment with Randomized Control Group Pretest-Posttest design and descriptive methods. The research sample was class X9 dan X10 semester 2 of Senior High Scool at Cimahi. Instruments that used were concept understanding test with CRI, observation form, student’s attitude scale form. N-gain average of understanding concept of experiment class is 0,50 and control class is 0,33. The result statistical test (test-t) showed improvement of concept understanding on students who use cmaptools in conceptual interactive learning was higher significantly compared with students who use conceptual interactive learning without cmaptools. Based on CRI analysis, the result were experiment class has more less misconception than control class. The result of student’s attitude scale was almost of all students agree that applying conceptual interactive learning with cmaptools media can motivate, gain concept understanding and can be applied for another concept in physics.